CPR and ECMO: The Next Frontier - Ambinder, Daniel I. (Rambam Maimonides Med J, 2020)
Cardiopulmonary resuscitation (CPR) is a first-line therapy for sudden cardiac arrest, while extracorporeal membrane oxygenation (ECMO) has traditionally been used as a means of countering circulatory failure. However, new advances dictate that CPR and ECMO could be complementary for support after cardiac arrest. This review details the emerging science, technology, and clinical application that are enabling the new paradigm of these iconic circulatory support modalities in the setting of cardiac arrest.